Consistent increase in the prevalence and female ratio of multiple sclerosis over 15 years in northern Japan. (24th November 2017) - Houzen, H.; Kondo, K.; Horiuchi, K.; Niino, M.
Abstract : Background and purpose: The prevalence of multiple sclerosis (MS) is considered to be lower in East Asia than in Western countries. An increasing trend has been reported globally for the prevalence of MS. We investigated the changes in the prevalence and clinical characteristics of MS in the Tokachi province of Hokkaido, northern Japan from 2001 to 2016. Methods: Prevalence was determined on 31 March 2016. Data‐processing sheets were collected from all MS‐related institutions in Tokachi province. We applied Poser's diagnostic criteria for MS as used in our previous three studies. Cases of neuromyelitis optica spectrum disorders were excluded. Results: In 2016, the crude MS prevalence was 18.6/100 000 (95% confidence interval, 14.3–23.8) in northern Japan. Over the last 15 years, the prevalence of MS in the same area was 8.1, 12.6 and 16.2 in 2001, 2006 and 2011, respectively. The female:male ratio was 3.57, which increased from 2.63 in 2001. The ratios of primary progressive, relapsing–remitting and secondary progressive MS types were 2%, 84% and 14%, respectively. Conclusion: Our results demonstrated a consistent increase in MS prevalence among the northern Japanese population, particularly in females, and relatively lower rates of progressive MS in northern Japan than in Western countries.